The return of the skulls (Tanzania, 2022): - (:unkn) unknown (My University, 2024)
During the colonial era, numerous African skulls were sent to be studied in museums in Europe, where craniology was in full swing. Today, the situation has been reversed, and African countries are increasingly requesting the return of cultural objects and human remains. In Tanzania in particular, some of these confiscated skulls have immense symbolic value because they are the remains of heroes of the anti-colonial resistance who were hanged in public and had no right to a burial. Their skulls were shipped to Germany under the Second Reich. After a long silence, their descendants are demanding that they be returned to bear witness to a past that is now viewed as glorious and to serve as a lesson for future generations. However, their restitution poses numerous problems, not only with regard to identification, but also in legal, political and financial terms. Here, we take stock of the situation in Tanzania and Germany, and offer a brief overview of the situation in other European countries.
Keywords: African Research